Encountering the sacred : the debate on Christian pilgrimage in late antiquity - Bitton-Ashkelony, Bruria (University of California Press, 2005)
This innovative study sheds new light on one of the most spectacular changes to occur in late antiquity--the rise of pilgrimage all over the Christian world--by setting the phenomenon against the wide background of the political and theological debates of the time.
Keywords: Christian pilgrims and pilgrimages -- Palestine -- History of doctrines -- Early church, ca. 30-600.; Palestine -- In Christianity -- History of doctrines -- Early church, ca. 30-600.; RELIGION -- Holidays -- Christian.; RELIGION -- Antiquities & Archaeology.; Middle East -- Palestine; 30 - 600